Molecular data suggest population expansion and high level of gene flow in the Plain Tiger (Danaus chrysippus; Nymphalidae: Danainae) - Vinaya Kumar Singh; P. C. Joshi; Bheem Dutt Joshi (Mitochondrial DNA. Part B. Resources, 2018)
In the present study, we sequenced the individuals of the Danaus chrysippus from the different altitudinal ranges in the western Himalayan state of Uttarakhand, India and compared with other global published data across its distribution range using the cytochrome oxidase c subunit-I (COI). Among the sequences generated in this study, we observed total six haplotypes with intra-species sequence divergence of 0.001–0.009. Whereas the combined data generated a total of 24 haplotypes. The genetic diversity and neutrality test indices suggested overall population expansion of the species. This has also been supported by the MJ Network as it shows the star-like topology and formation of one core haplotype with maximum frequency distribution to the multiple locations. Whereas, the phylogenetic tree shows mixing of the haplotype from the different locations to the same clade. Haplotype arrangement in both phylogenetic tree and MJ Network is not clustered as per their geographic affinity, which suggests incomplete lineage shorting and recent population expansion or colonizations to the new area.